Livestock Farmer Demography and Adaptive Capacity to Climate Change and Variability in Limpopo and Mpumalanga Province of South Africa - Tshikolomo, Khathutshelo A.; Nesamvuni, Azwihangwisi E.; Petja, Marema; van Niekerk, Johan; Mpandeli, Ndivhudza S. (Technium Social Sciences Journal, 2022)
The study investigated the demographic characteristics of smallholder livestock farmers in Limpopo and Mpumalanga Province of South Africa and their effect on the capacity of the farmers to adapt to climate change and variability. Respondents were mainly heads (58.7%) and parents (25.7%) to heads of households and were mostly male (63.4%) with good health (97.8%) associated with high adaptive capacity to climate change and variability. Regarding socio-economic status, four in five (81.5%) of the livestock farmers had only secondary education at most, and incomes were generally low, probably associated with low capacity to adapt to climate change and variability. On the contrary, the quality of housing for the livestock farmers was either top (48.5% of farmers) or medium (47.4%). Some 45.9% of farmers owned 4 to 5 rooms, 44.5% owned six or more rooms, with 88.5% of them having financed their houses. Almost all the respondents (97.3%) had access to electricity, and these suggest the high capacity to adapt to climate change and variability. With regards to aspects of livestock farming, one male (40.1% of households) and female (39.3%) member was fit to work in farming, livestock was owned by heads (52.9% of the households) and by children (29.0%), affirming the high capacity to adapt to climate change and variability. Almost all respondents (99.2%) used communal land, had fewer livestock, lacked training (99.5%), never belonged to a farmers’ union (99.7%) or a producer organization (100.0%), and had no access to financial support from the government (99.2%) associated with low adaptive capacity. The findings of the study revealed that demographic factors had different influences on the capacity of smallholder livestock farmers to adapt to adverse effects of climate change and variability on the farming enterprises. This was true for all the three types of demographic factors studied, namely: personal characteristics, economic status, and aspects of livestock farming.